Reaction discovery using acetylene gas as the chemical feedstock accelerated by the "stop-flow" micro-tubing reactor system. Issue 5 (13th March 2017) - Xue, Fei; Deng, Hongping; Xue, Chengwen; Mohamed, Dara Khairunnisa Binte; Tang, Karen Yuanting; Wu, Jie
Abstract : A "stop-flow" micro-tubing reactor system was designed for accelerating reaction discovery using flammable acetylene gas as the feedstock. Abstract : Acetylene gas has been applied as a feedstock under transition-metal catalysis and photo-redox conditions to produce important chemicals including terminal alkynes, fulvenes, and fluorinated styrene compounds. The reaction discovery process was accelerated through the use of "stop-flow" micro-tubing reactors. This reactor prototype was developed by joining elements from both continuous micro-flow and conventional batch reactors, which was convenient and effective for gas/liquid reaction screening. Notably, the developed transformations were either inefficient or unsuccessful in conventional batch reactors. Its success relies on the unique advantages provided by this "stop-flow" micro-tubing reactor system.